Assessing hydrologic response to climate change and human interference in the major river basins of Thailand - Dumagpi, Eunice Agtual; Natthachet Tangdamrongsub; Shrestha, Sangam; Sundaram, S. Mohana; Thai Pipe Scholarship; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Analysis of the long-term historical change in Thailand{u2019}s major rivers showed that human intervention is the main driver that caused streamflow alterations. Despite this finding, the influence of human intervention on future projections of water balance components have not been explored yet, and studies solely focused on climate change impact. The exclusion of human intervention in research works can be attributed to limited data availability on human management of water resources. Another limitation in hydrological analysis is the lack of ground observations brought by ungauged basins, which restricts investigation to a single catchment. Human impacts are not limited within a catchment only, hence multiple-basin analysis must be investigated. The growing availability and improvement of global data from satellites has led to the development of Global Hydrological Models (GHM). GHMs benefit from its utilization of global datasets for multiple basin analysis and its incorporation of human intervention into its model. This study aimed to assess the combined impact of climate change and human intervention over the historical and future water balance components on Thailand{u2019}s basins, with the aid of a GHM called Community Water Model (CWatM). The model was improved by using observational datasets on discharge, terrestrial water storage anomaly (TWSA), soil moisture, evapotranspiration, and groundwater. Projections of water balance components were done under scenarios SSP126, SSP370, and SSP585 for the period 2015 to 2100. The improved model yielded strong correlation with water balance components, consistently reaching a Pearson Correlation value of more than 0.5. In terms of projections, it was shown that there will be a decreasing trend in streamflow, coupled with the shifting of timing in maximum and minimum flows. TWSA is expected to decrease and reach negative values towards the mid-future, signifying constant hydrological drought from then on. Human intervention, in the form of water demand, exhibited a significant impact on these projected trends.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Water Engineering and Management, School of Engineering and Technology
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Hydrologic models; Hydrology -- Mathematical models; Hydrology -- Thailand